2020
DOI: 10.1007/978-3-030-20249-1_8
|View full text |Cite
|
Sign up to set email alerts
|

Education for Environmental Citizenship and Responsible Environmental Behaviour

Abstract: The notion of Environmental Citizenship embodies behaviour – an actively involved citizen who exercises his/her environmental rights and obligations in the private and public spheres. Education for Environmental Citizenship implies behavioural change; its goal is to facilitate an individual’s intellectual growth (cognitive domain) and emotional capacity (affective domain) that may lead to a critical and actively engaged individual. Human behaviour is overwhelmingly sophisticated, and what shapes pro-environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 44 publications
0
21
0
2
Order By: Relevance
“…Studies also show a positive effect of increased information on environmental behavior (e.g. Goldman et al, 2020) emphasizing the importance of informed citi en , hich is a commonl highlighted target of smart cities (Sodiq et al, 2019). It can hence be suggested that smart city targets accompanied with increased social capital development and emphasis on information guidance, may have a positive impact on sustainable transformation of cities: ultimately this could change households attitudes and increase their interest in carbon reduction, leading to more environmentally sustainable behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Studies also show a positive effect of increased information on environmental behavior (e.g. Goldman et al, 2020) emphasizing the importance of informed citi en , hich is a commonl highlighted target of smart cities (Sodiq et al, 2019). It can hence be suggested that smart city targets accompanied with increased social capital development and emphasis on information guidance, may have a positive impact on sustainable transformation of cities: ultimately this could change households attitudes and increase their interest in carbon reduction, leading to more environmentally sustainable behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Like in many previous questionnaire studies, self-reported past PEBs served as a dependent variable rather than a predictor of PEBs in this research. Accordingly, a review on the role of past behavior and formation of habits is omitted here as corresponding information is provided elsewhere [100].…”
Section: Past Behavior and Further Variables Determining Pebsmentioning
confidence: 99%
“…Researchers employ various theories and models to define consumers' sustainable behavior [28]. Nonetheless, Kollmuss and Agyeman [47] have suggested that, due to its complexity, the question of what forms environmentally friendly behavior is impossible to visualize using a single system or framework, as it might be too complicated or lose its applicability or meaning.…”
Section: Internal Antecedents Of Pro-environmental and Pro-social Engmentioning
confidence: 99%
“…Collective wellbeing-oriented individuals prioritize group goals over personal ones, and are more inclined to collaborate and engage in sustainable consumption, such as waste sorting. Janmaimool and Denpaiboon [27], Goldman et al [28] and Wang, Wang, Li and Yang [29] have analyzed the groups of factors determining pro-environmental engagement in sustainable consumption. Kadic-Maglajlic et al [11] provides substantiation for the influence of consumer's self-identity and values on pro-environmental and pro-social engagement in sustainable consumption.…”
Section: Introductionmentioning
confidence: 99%